Identification of Sustainability Course Topics Relevant to the Needs of Airport Professionals - Haidar, Muhammad Farras; Indriyanto, Toto (Langit Biru: Jurnal Ilmiah Aviasi, 2025)
This research is based on the condition of environmental degradation and public awareness of climate change caused by industry after the Paris Agreement held in 2015. One industry that causes environmental damage is the aviation industry. Increased awareness of the impact generated has made the aviation industry begin to improve to reduce emissions. This research focuses on identifying sustainability course topics relevant to airport professionals to improve their competency in dealing with environmental issues. This research uses Natural Language Processing (NLP) methods, where the NLP used is Unsupervised Learning, especially Latent Dirichlet Allocation (LDA). LDA was used to search for hidden topics in a set of airport sustainability reports accredited by Airport Carbon Accreditation (ACA). ACA is a globally recognized institutional carbon management certification program for airports. The analysis results show that the professional training topics related to green finance for sustainable airports match the current market needs and are not yet organized by course providers at leading international aviation organizations.